2006
DOI: 10.1017/s095026880600608x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia due to ciprofloxacin-resistant Salmonella enterica serotype Choleraesuis in adult patients at a university hospital in Taiwan, 1996–2004

Abstract: Eighty-one adult patients with Salmonella enterica serotype Choleraesuis (S. Choleraesuis) bacteraemia treated at a university hospital from 1996 to 2004 were evaluated. Multivariate analysis with a logistic regression model was used to characterize risk factors for primary bacteraemia and mycotic aneurysm and to determine the association of clinical characteristics of patients based on ciprofloxacin susceptibility of the causative organism. The incidence per 100,000 discharges was 0.76 in 1996 and 3.9 in 2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…We found a very high prevalence of antimicrobial resistance among the nontyphoid Salmonella isolates from outpatients in Henan Province compared to what has been reported in North America and Europe (2,5,10,12,19,22,23,27,29). In particular, we found that 54% of all isolates were resistant to ciprofloxacin and 23% were highly resistant.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…We found a very high prevalence of antimicrobial resistance among the nontyphoid Salmonella isolates from outpatients in Henan Province compared to what has been reported in North America and Europe (2,5,10,12,19,22,23,27,29). In particular, we found that 54% of all isolates were resistant to ciprofloxacin and 23% were highly resistant.…”
Section: Discussionsupporting
confidence: 45%
“…This was especially evident among S. enterica serovars Indiana, Enteritidis, and Typhimurium, among which 100%, 97%, and 89%, respectively, were ciprofloxacin resistant. Reports from other countries have found an increasing frequency of ciprofloxacin-resistant isolates (2,10,19,22,23,27,29) but not a frequency approaching that observed in Henan Province. Infections with ciprofloxacin-resistant isolates are associated with increased morbidity and mortality (16,17,28), and the alarmingly high frequency makes it difficult to use fluoroquinolones for treatment of Salmonella infections in humans.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the USA and Europe, community-acquired meticillin-resistant Staphylococcus aureus (MRSA) [1], vancomycin-resistant enterococci (VRE) [2], Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae [3] and fluoroquinolone-and carbapenemresistant Pseudomonas aeruginosa [4] have spread throughout community and hospital settings. In striking contrast, high prevalence rates of penicillin-resistant Streptococcus pneumoniae [5,6], ␤-lactamase-negative ampicillin-resistant (BLNAR) Haemophilus influenzae [7,8], carbapenem-non-susceptible Acinetobacter baumannii [9][10][11], extended-spectrum ␤-lactamase (ESBL)-producing K. pneumoniae [12,13], New Delhi metallo-␤-lactamase 1 (NDM-1)-producing Enterobacteriaceae [14], multidrug-resistant (MDR) Salmonella enterica serotypes Choleraesuis and Typhi [15][16][17], azole-resistant Candida spp. (particularly Candida glabrata) [18] and extensively drug-resistant Mycobacterium tuberculosis (XDR-TB) [19,20] are commonly reported in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In 10 European countries a survey conducted in 2000 identified a cefotaxime resistance rate of 0.6% in Salmonella isolates recovered from human sources (Threlfall et al, 2000). In recent years, such a trend of increase in drugresistant salmonellae including resistance to quinolones has been observed in many countries, particularly in Asia (Lauderdale et al, 2006;Wang et al, 2006). The use of antimicrobials in any purpose, including disease treatment and growth promotion in domestic livestock, can potentially lead to develop drug resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%